Strategic Partnerships: Mediating Service Diversification and Environmental Performance for Waste Management Sustainability in Cement Company - Setiawan, Agus; Agung Martono , Besar (Journal Research of Social Science, Economics, and Management, 2026)
This research investigates the role of strategic partnership as a mediator in the relationship between service diversification, environmental performance, and sustainability in waste management within the cement industry, focusing on PT Bangun Jaya Indonesia Tbk (AFR Division). This research aims to analyze the direct effect of service diversification and environmental performance on sustainability business, examine their direct effect on strategic partnership, test the direct effect of strategic partnership on sustainability business, and analyze the mediating role of strategic partnership in the relationship between service diversification and environmental performance on sustainability business. Using a quantitative approach with a correlational and experimental design, data were collected from all 121 employees using a structured questionnaire and supported by secondary data from company reports. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to analyze direct and mediated relationships among variables. The results indicate that service diversification does not directly affect sustainability business performance but significantly influences strategic partnerships. Environmental performance directly contributes to sustainability business but does not significantly affect strategic partnerships. Strategic partnerships have a positive and significant direct effect on sustainability business and mediate the impact of service diversification. However, strategic partnerships do not mediate the effect of environmental performance, as environmental initiatives are implemented independently by the company. These findings highlight the critical role of strategic partnerships in translating service diversification into sustainable business outcomes, while environmental performance operates directly. The research provides empirical evidence for cement companies to leverage partnerships strategically to enhance sustainable operational performance in waste management.